The accuracy of a 3-D laser scanner for crown width measurements - Nouri Mahtab; Massudi Reza; Bagheban Alireza Akbarzadeh; Azimi Somayyeh; Fereidooni Farzad (Sciendo, 2023)
Virtual dental casts have been recently introduced to orthodontics. The problem of capturing the shapes of teeth on study casts may be complicated by the presence of undercut areas and deep grooves.